PENGARUH MARKETING MIX DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN DI O’OCONG PANCING AMBULU - Maharani, Andhika Putra Andryan; Fatimah, Feti; Izzudin, Ahmad (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
A high level of purchase of a product is proof that a business is growing well. So a company is required to always be innovative in marketing products at affordable costs that are attractive to consumers. Similarly, because of the rise of similar businesses, O'ocong Pancing, which is engaged in trade, must plan an appropriate strategy. Therefore, this research was conducted to examine the appropriate strategy for the company. The purpose of this research is to examine the influence of the marketing mix and service quality on purchasing decisions. There are five dimensions used for the marketing mix, namely: (X1) product, (X2) price, (X3) place, (X4) promotion, and (X5) service. The research uses quantitative methods, and 130 samples are involved with the criteria of consumers of O'ocong Pancing. After the data is collected, it is tested using multiple linear regression with the T test as a hypothesis test. The results showed that there was a significant positive effect of service on purchasing decisions. Promotion, place, price, and product dimensions do not significantly affect the partial decision.